Thermomechanical stress analyses of nanowarming-assisted recovery from cryopreservation by vitrification in human heart and rat heart models. - Purva Joshi; Yoed Rabin (PLoS ONE, 2023)
This study investigates thermomechanical stress in cryopreservation by vitrification of the heart, while exploring the effects of nanowarming-assisted recovery from cryogenic storage. This study expands upon a recently published study, combining experimental investigation and thermal analysis of cryopreservation on a rat heart model. Specifically, this study focuses on scenarios with variable concentrations of silica-coated iron-oxide nanoparticles (sIONPs), while accounting for loading limitations associated with the heart physiology, as well as the properties of cryoprotective agent (CPA) solution and the geometry of the container. Results of this study suggest that variable sIONP concentration based on the heart physiology will elevate mechanical stresses when compared with the mathematically simplified, uniform distribution case. The most dangerous part of rewarming is below glass transition and at the onset of nanowarming past the glass transition temperature on the way for organ recovery from cryogenic storage. Throughout rewarming, regions that rewarm faster, such as the chambers of the heart (higher sIONP concentration), undergo compressive stresses, while the slower rewarming regions, such as the heart myocardium (low sIONP concentration), undergo tension. Being a brittle material, the vitrified organ is expected to fail under tension in lower stresses than in compression. Unfortunately, the location and magnitude of the maximum stress in the investigated cases varied, while general rules were not identified. This investigation demonstrates the need to tailor the thermal protocol of heart cryopreservation on a case-by-case basis, since the location, orientation, magnitude, and instant at which the maximum mechanical stress is found cannot be predicted a priori. While thermomechanical stress poses a significant risk to organ integrity, careful design of the thermal protocol can be instrumental in reducing the likelihood of structural damage, while taking full advantage of the benefits of nanowarming.